(untitled) (Revista Innova Educación, 2024)
This review paper addresses the need to infuse intercultural learning in the language classroom. The body of literature offers evidence of language approaches and methods that can potentially benefit the foreign/second language classroom by shifting from traditional practice to more active, participatory, and interculturally infused teaching. Teaching a foreign/second language comprehensively requires the inclusion of the intercultural component to equip learners with the ability to interact in increasingly intercultural contexts. Therefore, this paper proposes a model to design language and intercultural tasks in the language classroom. The methodology applied in this paper is based on a qualitative approach by reviewing the literature to gather insights to facilitate an intercultural approach based on a hybrid pedagogy merging Content and Language Integrated Learning (CLIL) and Project-based Learning (PBL), designing a model to implement an intercultural language experience centered on learners. Results suggest that language educators can provide positive learning opportunities for students to develop intercultural competence when planning and mediating intercultural language tasks in the foreign/second language classroom. Language learners can amplify their competencies and language skills in more authentic and meaningful ways when the instruction is infused with intercultural elements. The design described can serve as an intercultural language model to teach and develop intercultural communicative competence intended to improve communication across cultures.